Faktor-Faktor Yang Mempengaruhi Kepuasan Kerja Karyawan PT. Trimegah Cipta Mandiri - Amandin Amandin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Job satisfaction reflects a person's feelings about his job. The purpose of this study was to determine the factors that affect employee job satisfaction at PT. Trimegah Cipta Mandiri Farm 2 Talang Taling Village, Gelumbang District. The factors in question are the variables of leadership and motivation. This type of research is a survey research with a descriptive quantitative approach. The population is all employees of PT. Trimegah Cipta Mandiri Farm 2 Talang Taling Village, Gelumbang District, the sample was taken 56 people, with a random sampling technique with a saturated sample method. This study uses primary data obtained from respondents' answers in the form of filling out questionnaires, namely data obtained directly from the research object. Data analysis techniques include: instrument testing consisting of validity and reliability tests, classical assumption tests consisting of normality, multicollinearity, and heteroscedasticity tests, multiple linear regression tests and hypothesis testing consisting of the F test, the coefficient of determination test and the t test. The results of the research for the determination test showed an R Square of 0.803. This shows that the leadership and motivation variables simultaneously have an influence of 0.803 or 82.4% on job satisfaction, while the remaining 19.7% is the influence of (aspects) or other factors not included in the study, for example training variables, performance etc. While the correlation value (R) = 0.789. This shows that the variables of leadership and motivation have a very strong correlation to Job Satisfaction. Keywords: Leadership, Motivation and Job Satisfaction